Thoracoscopic repair of congenital diaphragmatic hernia in infants: a dual-suture approach using barbed and non-absorbable sutures - Shang, Xianhui; Liu, Yuanmei; Luo, Zhen; Li, Yingbo; Zhou, Guangxu; Tan, Hongyang; Mao, Kaiyi (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the feasibility, safety, and clinical efficacy of a dual suture technique combining barbed suture and non-absorbable needle suture in thoracoscopic repair of congenital diaphragmatic hernia (CDH) in children.MethodsA retrospective analysis was conducted on 48 pediatric patients who underwent thoracoscopic CDH repair at our institution between March 2012 and August 2024. Based on the suturing method used, patients were divided into an observation group (barbed suture combined with non-absorbable needle suture, n = 21) and a control group (non-absorbable needle suture alone, n = 27). Perioperative indicators including operative time, intraoperative blood loss, chest tube duration, postoperative hospital stay, and arterial blood gas values (pH, PO₂, PCO₂) before and after surgery were compared between groups. Postoperative complications such as suture loosening or hernia recurrence during follow-up were also assessed.ResultsAll procedures were successfully completed thoracoscopically with no conversions to open surgery. Operative time was significantly shorter in the observation group compared to the control group [(37.2 ± 7.3) min vs. (65.8 ± 12.4) min]. No significant differences were found between the two groups in terms of blood loss, chest tube duration, postoperative hospital stay, or blood gas parameters (all P > 0.05). During a follow-up period of 6–24 months (median 12 months), no cases of suture loosening, hernia recurrence, or mortality were observed in either group.ConclusionThe dual suture technique combining barbed suture with non-absorbable needle suture is safe and effective in thoracoscopic repair of CDH in children. It significantly reduces operative time without increasing the risk of postoperative complications or recurrence. This technique is suitable for promotion in institutions with appropriate thoracoscopic expertise.